2018
DOI: 10.1002/glia.23326
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of Α7 nicotinic receptors as a novel method to monitor neuroinflammation after cerebral ischemia

Abstract: In vivo positron emission tomography (PET) imaging of nicotinic acetylcholine receptors (nAChRs) is a promising tool for the imaging evaluation of neurologic and neurodegenerative diseases. However, the role of α7 nAChRs after brain diseases such as cerebral ischemia and its involvement in inflammatory reaction is still largely unknown. In vivo and ex vivo evaluation of α7 nAChRs expression after transient middle cerebral artery occlusion (MCAO) was carried out using PET imaging with [ C]NS14492 and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Nevertheless, a recent study showed that the daily treatment of PHA 568487 during the first week after transient cerebral ischemia in rats displayed a nonsignificant decrease of the expression marker values for both proinflammatory and anti-inflammatory microglia markers. 22 Moreover, this study observed fewer values of selectines, adhesion molecules and infiltrated T lymphocytes after treatment with PHA, suggesting a possible role of α7 nAChRs in the regulation of leukocyte infiltration into the ischemic tissue. 22 Likewise, the infiltration of leukocytes after stroke can also be influenced by the disruption of the BBB; however, activation of α7 receptors showed similar levels of BBB disruption after MCAO in rats.…”
Section: Cholinergic Receptorsmentioning
confidence: 54%
See 3 more Smart Citations
“…Nevertheless, a recent study showed that the daily treatment of PHA 568487 during the first week after transient cerebral ischemia in rats displayed a nonsignificant decrease of the expression marker values for both proinflammatory and anti-inflammatory microglia markers. 22 Moreover, this study observed fewer values of selectines, adhesion molecules and infiltrated T lymphocytes after treatment with PHA, suggesting a possible role of α7 nAChRs in the regulation of leukocyte infiltration into the ischemic tissue. 22 Likewise, the infiltration of leukocytes after stroke can also be influenced by the disruption of the BBB; however, activation of α7 receptors showed similar levels of BBB disruption after MCAO in rats.…”
Section: Cholinergic Receptorsmentioning
confidence: 54%
“… 22 Moreover, this study observed fewer values of selectines, adhesion molecules and infiltrated T lymphocytes after treatment with PHA, suggesting a possible role of α7 nAChRs in the regulation of leukocyte infiltration into the ischemic tissue. 22 Likewise, the infiltration of leukocytes after stroke can also be influenced by the disruption of the BBB; however, activation of α7 receptors showed similar levels of BBB disruption after MCAO in rats. 22 In contrast, Zou and colleagues examined the effect of α7 nAChRs activation with PHA after cerebral ischemia in mice showing an improvement of the BBB integrity.…”
Section: Cholinergic Receptorsmentioning
confidence: 54%
See 2 more Smart Citations
“…Expression levels of α7nAChR have been investigated in various inflammatory models. On one hand, an increase of α7nAChR expression in both microglia and astrocytes was reported in cerebral ischemia in rats, leading to microglial activation and pro-inflammatory cytokine production (Niranjan et al, 2012;Wu L. et al, 2014;Colás et al, 2018). This was counteracted by nicotine treatment, which reduced pro-inflammatory cytokine production as well as microglial activation, and also prevented neuronal death in the CA1 region of the hippocampus in rats (Guan et al, 2015).…”
Section: The Interaction Between Cholinergic Neurons and Glial Cells-mentioning
confidence: 98%